Cine musical español 1975-80 - Blanco Mallada, Lucio (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2006)
This article intends to envisión what the musical cinema was in the second half of the seventies in the environment of the cinema and of the changes that were happening in the political ans social conditions of the country. So, the mixture of politics and business were the normal attitude due to times of perplexity of the cinema looking out and looking inside itself ang going opposite directions in the same way. Nostalgy and will of living behind the past are the lines to describe the situatión of the musical cinema, maybe all the cinema, of the periode.
Keywords: Musical cinema; Code; Semiotic